Types of institutional investors and earnings management in Malaysia - Bamahros, Hasan Mohammed; Wan Hussin, Wan Nordin (American Scientific Publishers, 2015)
The main objective in this study is to investigate the association between types of institutional investors and the level of discretionary accruals in Malaysian public listed firms.Two measurements, namely discretionary current accruals based on the performance-adjusted model and discretionary total accruals based on modified Jones model are used to estimate the levels of discretionary accruals. Our sample consists of 525 companies listed on Bursa Malaysia for financial year 2009.The results suggest that short-term institutional investors exacerbate discretionary accruals.However, long-term institutional investors do not have significant relationship with the level of discretionary accruals in Malaysia.